OPTIMIZATION OF 3D LOCAL ORIENTATION MAP CALCULATION IN THE MATLAB FRAMEWORK - Al Darwich, Ranya; Babout, Laurent (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
This paper presents the development and evaluation of a new approach toward the optimization of 3D local orientation map calculation in the Matlab framework. This new approach can be detailed as: optimize eigenvector calculation for PCA analysis of X-ray micro tomography images of lamellar Titanium alloys image. We use two different methods to find the eigenvector of the largest eigenvalue and compare them with the Matlab built-in function (eigs). The results show a steep decrease of the calculation time using the authors' method compared to the Matlab built-in function.